(untitled) (Jurnal Kemanusiaan, 2017)
The family institutiton has undergone drastic changes as a consequence to changes of roles, family size, parent’s level of education and system of family communication. even through the importance of family institution roles cannot be denied, most families no longer adhere to their traditional roles. Their roles have been taken over by other socialization agents such as the schools, police, religious department, rehabilitation centers, maid and etc. Initially, transition aims to minimize the role of family also contribute toward the second-generation social problem. This problem level of severity varies across type of occupations, level of education and mass media influence. Uncomfortable household also has been suggested as a factor that causes weak family relationship. Weak family relations brings to the social problem faced by the second generation. In this paper, five (5) prominent family problems in Malaysia will be highlighted.These problems are: divorse, single mother, wife abuse, child abuse and juvenile. Discussion will focus on the factors that cause the problems and related issues to the problem. Solutions in term of counseling and other relevant approaches are recommended to reduce the problems.